Le journalisme comme récit théorisé du militantisme chez Teresa Billington-Greig (Grande-Bretagne, 1877-1964) - Myriam Boussahba-Bravard (Genre & Histoire)
Teresa Billington-Greig was an English suffragist that denounced political and physical violence targeted at women before 1914. When she was successively a member of various suffragist organisations, she decidedly “voiced” and wrote that women should always repulse men’s practical, political and metaphoric violence, even if women had to transgress social norms prescribing their behaviour to do so. In her political struggle, she never separated ordinary grassroots suffragist activism from her militant journalistic writings. When her feminist commitment made her drop her suffragist activities, she unsuccessfully tried to have a press career as a feminist writer before and after the First World War She could not make a living out of journalism that had newly opened to women but that still confined them to items called ‘feminine’. Although she meant to upset established norms in the political world as well as in journalism, she did not succeed. She could be perceived as a failure by her contemporaries; however, in a historical perspective, she certainly followed an emblematic route, rejecting women’s expected silence, all the same without making her voice heard that long.